Prinsip Hukum Ekonomi Syariah Dalam Tata Kelola Fintech Syariah Berbasis Teknologi Digital di Indonesia - WIDIANTARI, BAIQ (Fakultas Hukum Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2025)
This study aims to analyze the regulation of Islamic fintech in Indonesia based on the principles of Islamic economic law, assess the consistency of regulations within the national legal system, and evaluate regulations based on the maqāṣid al-sharī‘ah to realize the benefit and legal certainty. This study uses a normative legal approach with an analysis of primary, secondary, and tertiary legal materials through grammatical, systematic, and teleological interpretations. The results show that first, the regulation of Islamic fintech has been framed in the Islamic Banking Law, OJK regulations, and DSN-MUI Fatwas, so that every Islamic fintech activity must comply with the principles of justice, benefit, legal certainty, and freedom of contract that are limited by sharia. Second, regulatory consistency requires the integration of legal norms, supervisory structures, and legal culture, so that regulatory fragmentation does not create uncertainty for business actors or service users. Third, from the perspective of maqāṣid al-sharī‘ah, this regulation guarantees the benefit, legal certainty, and protection of the rights of all parties. The success of Sharia fintech regulation is measured by the integration of positive law, the principles of Sharia economic law, and maqāṣid al-sharī‘ah, thus creating an orderly, fair, and sustainable Sharia digital financial ecosystem.